SIMPLE ADDITIVE WEIGHTING DALAM PERANAN TEKNOLOGI INFORMASI SEBAGAI FUNGSI KONTROL PENGAWASAN PEMBANGUNAN PADA PROGRAM DMIJ - Muh Rasyid Ridha (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
The village of Nusantara Jaya is a village located in Keritang district of Indragiri Hilir district, a village with eleven villages that are fairly large villages that require quite complex controls. With the program of DMIJ (Desa Maju Inhil Jaya) which is the flagship program of Indragiri downstream government to help the villages to be more advanced and rapidly development it is necessary a decision support system to determine the development fund of Nusantara Jaya village. In the process of developing the decision support system of determining the village development fund using Simple Additive Weighting (SAW) method, this method is chosen because it’s able to select the best alternative from a number of alternative locations (hamlet) which will be prioritized as the recipient of the development fund based on the criteria specified. Research is done by finding the weight value for each attribute, then done the ranking process and determine the alternative (optimal) is the best location. Based on the analysis, it can be seen that the recommended locations as beneficiaries are ranked according to the highest as follows: (1) Teluk Dalam 0,95, (2) Gemilang Utama 0,84, (3) Nurul Iman 0,84, (4) Selamat Abadi 0,83, (5) Pinang Teluk 0,82, (6) Nusantara 10,8, (7) Sungai Bulan 0,77, (8) P.4.S Riau 0,76, (9) Amanah 0,70, (10) Makmur 0,68, and (11) Usaha Damai 0,55.